2022
DOI: 10.4995/riai.2022.16652
|View full text |Cite
|
Sign up to set email alerts
|

Control no-híbrido de glucemia ensayado en pacientes ambulatorios con Diabetes Tipo 1

Abstract: En este trabajo se presenta la experiencia argentina en el problema de regulación de los niveles de glucosa en sangre para pacientes con Diabetes Mellitus Tipo 1 (insulino-dependientes), denominado Páncreas Artificial. El grupo de trabajo ha realizado 3 pruebas clínicas, las primeras en Latinoamérica. Las dos primeras fueron concretadas en 2016 y 2017, ambas en el Hospital Italiano con 5 pacientes adultos durante 36 hs. En la segunda de ellas se utilizó un nuevo algoritmo de control de lazo cerrado puro (sin b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Patient acceptance was generally high, whereas provider acceptance was lower, highlighting the need for more telemedicine training in medical education. Although a few studies reported that telehealth performs comparably to in-person primary care, 76,101,131 the evidence remains limited regarding its clinical effectiveness, cost-effectiveness, and long-term sustainability. 132,133 Also, structural barriers around health literacy and digital skills (particularly among elderly patients), insufficient availability of technology, limited infrastructure, and suboptimal connectivity (particularly in rural and poorer regions) can be issues.…”
Section: Discussionmentioning
confidence: 99%
“…Patient acceptance was generally high, whereas provider acceptance was lower, highlighting the need for more telemedicine training in medical education. Although a few studies reported that telehealth performs comparably to in-person primary care, 76,101,131 the evidence remains limited regarding its clinical effectiveness, cost-effectiveness, and long-term sustainability. 132,133 Also, structural barriers around health literacy and digital skills (particularly among elderly patients), insufficient availability of technology, limited infrastructure, and suboptimal connectivity (particularly in rural and poorer regions) can be issues.…”
Section: Discussionmentioning
confidence: 99%